Филологик таълимдан бошқа гуруҳларда рус тилига оид дидактик материаллардан фойдаланиш методикаси - Атажанова, Г.Ю. (SCIENCE and SOCIETY, 2020)
The article contains information about some aspects of teaching the Russian language. Based on the goals and objectives of language acquisitions in modern conditions, the author has described in detail certain teaching methods.